Ursodeoxycholic acid therapy and liver transplant-free survival in patients with primary biliary cholangitis - Harms, Maren H.; van Buuren, Henk R.; Corpechot, Christophe; Thorburn, Douglas; Janssen, Harry L.A.; Lindor, Keith D.; Hirschfield, Gideon M.; Parés, Albert; Floreani, Annarosa; Mayo, Marlyn J.; Invernizzi, Pietro; Battezzati, Pier Maria; et al. (Journal of hepatology, 2019)
[Display omitted] •Ursodeoxycholic acid is associated with prolonged survival in primary biliary cholangitis.•This positive association is significant irrespective of age, sex, or disease stage.•The association remains significant in cases where the established criteria for therapeutic response are not met. The clinical efficacy of ursodeoxycholic acid (UDCA) in primary biliary cholangitis (PBC) remains subject to debate as definitive randomized controlled trials are lacking. We aimed to determine whether UDCA prolongs liver transplant (LT)-free survival in patients with PBC. This international cohort study included patients from the Global PBC Study Group database, originating from 8 countries in Europe and North America. Both UDCA-treated and untreated patients were included. LT and death were assessed as a combined endpoint through Cox regression analyses, with inverse probability treatment weighting (IPTW). In the 3,902 patients included, the mean (SD) age was 54.3 (11.9) years, 3,552 patients (94.0%) were female, 3,529 patients (90.4%) were treated with UDCA and 373 patients (9.6%) were not treated. The median (interquartile range) follow-up was 7.8 (4.1–12.1) years. In total, 721 UDCA-treated patients and 145 untreated patients died or underwent LT. After IPTW, the 10-year cumulative LT-free survival was 79.7% (95% CI 78.1–81.2) among UDCA-treated patients and 60.7% (95% CI 58.2–63.4) among untreated patients (p <0.001). UDCA was associated with a statistically significant reduced risk of LT or death (hazard ratio 0.46, 95% CI 0.40–0.52; p <0.001). The hazard ratio remained statistically significant in all stages of disease. Patients classified as inadequate biochemical responders after 1 year of UDCA had a lower risk of LT or death than patients who were not treated (adjusted hazard ratio 0.56; 95% CI 0.45–0.69; p <0.001). The use of UDCA improves LT-free survival among patients with PBC, regardless of the disease stage and the observed biochemical response. These findings support UDCA as the current universal standard of care in PBC. In this international multicenter study of 3,902 patients with primary biliary cholangitis, we found that treatment with ursodeoxycholic acid is associated with prolonged liver transplant-free survival. This association was significant, irrespective of sex, age, or disease stage. The survival benefit remained statistically significant in patients with an incomplete biochemical response to ursodeoxycholic acid therapy.